Collaborative General Practitioner Shared Care Versus Self-Directed Care Following Critical Illness in Young Children: A Pilot Hybrid Effectiveness-Implementation Randomized Controlled Trial - Debbie A. Long; Zephanie Tyack; Lori Anthony; Belinda Dow; Leigh Dunn; Renate Le Marsney; Trang M. T. Pham; James Best; Kerri-Lyn Webb; Helen Liley; Christian Stocker; Debra Thoms; et al. (Pediatric Critical Care Medicine, 2026)
Objectives: Up to one in three PICU survivors experience persistent developmental or psychologic challenges, and parents often report significant psychologic distress. Current health systems lack standardized pathways to support children and families after PICU. We aimed to assess the feasibility of a randomized controlled trial (RCT) of a collaborative general practitioner (GP) shared-care follow-up model of care intervention and the feasibility, acceptability, and appropriateness of the intervention. Design: Multicenter, pilot, hybrid effectiveness-implementation study with parallel RCT. Trial registration: Australian and New Zealand Clinical Trials Registry, ACTRN12621000799853, June 24, 2021. Setting: Two PICUs in Queensland, Australia. Participants: Parents of children admitted to PICU from ages 2 months or older to younger than 4 years. Interventions: Participants were randomized (1:1, web-based block randomization schedule) to 6 months of GP shared care (intervention) or self-directed care (active control). Measurements and Main Results: The primary outcome was trial feasibility. Secondary effectiveness and implementation outcomes included child neurodevelopmental vulnerability and parent psychosocial outcomes at 6 months and parental perception of the feasibility, acceptability, and appropriateness of the intervention, respectively. Between October 2021 and March 2023, 154 of 363 eligible parents (one per family) provided consent (42%); 69 were randomized to the intervention, and 72 to active control. Most parents were mothers (95%), 31–40 years old (54%), from metropolitan areas (72%). Children were predominantly male (64%), younger than 12 months old (41%), admitted for respiratory illness (39%). Retention (81%), fidelity (96%), and intervention acceptability was high (71–86%), but recruitment was low (42%) and intervention feasibility varied (35–82%). At 6 months, neurodevelopmental vulnerability rates were similar (shared care [39%] vs. active control [44%]; adjusted odds ratio (aOR), 0.72 [95% CI, 0.32–1.60]). Parenting stress was lower in the intervention group (median, 20 [interquartile range (IQR), 12–47]) vs. active control (median, 42 [IQR, 19–66]; difference, –23 [95% CI, –40 to –6]). Conclusions: A trial of a collaborative GP-shared-care model of care post-PICU is feasible and may reduce parenting stress. Further intervention refinement and a larger trial are warranted to evaluate clinical effectiveness, implementation, and scalability.